Hubungan Antara Fungsi Keluarga dengan Kejadian Sindrom Pramenstrual pada Siswi SMA N 2 Klaten - Janitra, Rizki Arya, dr. Yusuf Alam Romadhon, M.Kes, dr. Endang Widhiyastuti (2015)
Background Family function is a family duty involves caring, socialization, as well as solving health problem. Family influenced much in dealing with girl adolescents reproduction health problem. Reproduction health problem especially girls is strongly related to menstruation. In girl adolescents the sexual maturation was marked by first period or menarche. Girls adolescents with usually related to premenstrual syndrome (PMS). PMS is a group of symptoms both physically, psychologically, that occurred 7 days before period and happen in adolescents. Objective This study aimed to know the association between family function with premenstrual syndrome prevalence in girl adolescents of SMA N 2 Klaten. Methods This study used cross sectional methods, 50 samples is taken using purposive sampling in girl students of XI IPA. Family function data using APGAR family questionnaire and PMS prevalence using SPAF questionnaire. Result In this study, 7 girl students had PMS, data analyzed using spearman test. The result shows p value = 0,000 ( p < 0,001) and r value = 0,555. So there was significant association. Conclusions There is association between family function with premenstrual syndrome prevalence in girl students of SMA N 2 Klaten.